Effects of Systemic Enalapril Treatment on Skin andPeritendinous Adhesion: An Experimental Study - Bal, Ali; Altun, Serdar; Gurger, Murat; Orhan, Erkan; Kılıçarslan, Ahmet; Çakır, Fatih; Özcan, Erhan Cahit (My University, 2021)
Objective: One of the most important clinical complications after tendon repair surgery is fibrosisand adhesion formation, and some studies have shown that angiotensin II is responsible forpathological scarring and fibrosis. Enalapril, an angiotensin-converting enzyme inhibitor, inhibitsexcessive fibrosis and hypertrophic scarring while reducing conversion to angiotensin II. However,the effects of enalapril on skin fibrosis and peritendinous adhesion on tendon injuries remainunknown. We aimed to investigate the effects of enalapril on peritendinous adhesion and skinfibrosis during the extrinsic healing period of the tendon. Materials and Methods: Twenty-one rats were randomly divided into three groups: sham (GroupS), control (Group C) and enalapril (Group E). Both hindlimbs were operated. In Group S, theAchilles tendon was disassembled so that only the tendon sheath was opened. In groups C and E,the Achilles tendon was transversally and completely cut and then repaired. Postoperatively, onlyGroup E was provided enalapril treatment for 28 d via oral gavage. Full-thickness Achilles tendonbiopsies with skin were taken from healing regions to evaluate peritendinous adhesion and skinfibrosis.Results: The formation of skin fibrosis, but not of peritendinous adhesion, was significanly lower inthe enalapril group.Conclusion: Enalapril reduces fibrosis in skin or subcutaneous tissues but has no significant effecton epitendineum and tendon structure.
Keywords: Biyokimya ve Moleküler Biyoloji; İmmünoloji; Cerrahi; Ortopedi